2000
DOI: 10.1073/pnas.97.24.13057
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibition interferes with Gag polyprotein processing, release, and maturation of HIV-1 and HIV-2

Abstract: Retrovirus assembly and maturation involve folding and transport of viral proteins to the virus assembly site followed by subsequent proteolytic cleavage of the Gag polyprotein within the nascent virion. We report that inhibiting proteasomes severely decreases the budding, maturation, and infectivity of HIV. Although processing of the Env glycoproteins is not changed, proteasome inhibitors inhibit processing of Gag polyprotein by the viral protease without affecting the activity of the HIV-1 viral protease its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
298
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(334 citation statements)
references
References 25 publications
30
298
3
Order By: Relevance
“…However, Tsg101 UEV motif binds also to the P(T͞S)AP motif in the L domain of HIV-1 Gag polypeptide, and the crystal structure analysis revealed that the UEV domain can bind both Ub and PTAP peptide simultaneously (48). The observation that ISG15 interferes with ubiquitination of Gag and consequent release of virus particles correlates with the previous observation, which showed the inhibition of HIV-1 release in the presence of proteasome inhibitors (49).…”
Section: Discussionsupporting
confidence: 76%
“…However, Tsg101 UEV motif binds also to the P(T͞S)AP motif in the L domain of HIV-1 Gag polypeptide, and the crystal structure analysis revealed that the UEV domain can bind both Ub and PTAP peptide simultaneously (48). The observation that ISG15 interferes with ubiquitination of Gag and consequent release of virus particles correlates with the previous observation, which showed the inhibition of HIV-1 release in the presence of proteasome inhibitors (49).…”
Section: Discussionsupporting
confidence: 76%
“…This treatment was unable to rescue the cell-surface expression of BST-2 reduced by Vpu (supplemental Fig. S2C), suggesting that the reduced virion production in the presence of the protease inhibitor is not due to a recovery of the cell-surface expression of BST-2 but probably due to, as previously reported, the proteasome-inhibitor-induced reduction of virion release independently of Vpu, resulting from the rapid depletion of the free ubiquitin pool with prolonged drug treatment (52). Because of the unavailability of antibodies against cytoplasmic proteasome markers for immunofluorescence staining, we are unable to perform parallel experiments with treatment of lysosome inhibitors that showed colocalization of Vpu, BST-2, and the lysosome marker cathepsin D. We, therefore, cannot rule out that some fractions of BST-2 might be proteasomally degraded by Vpu.…”
Section: Discussionmentioning
confidence: 52%
“…Consequently, a subpopulation of retroviral Gag (ϳ2%) and VP40 is believed to become monoubiquitinated (17,18,47,57,58). This step is crucial in late stages of retroviral budding, since preventing Nedd4 ubiquitin ligases from functioning by using WW dominant-negative fragments (26,46,65) or by using proteasome inhibitors that reduce the amount of free ubiquitin in the cytoplasm (43,47,55) and monoubiquitination (43) inhibits viral budding and release. This defect can be partially corrected in the case of RSV by fusing ubiquitin to Gag polyprotein carrying a functional L-domain motif (47).…”
Section: Discussionmentioning
confidence: 99%
“…E3 ubiquitin ligases of the Nedd4 family were shown to be involved in budding of RSV and MPMV retroviruses (26,48,66). Proteasome inhibitors were found to interfere with the release of HIV-1 (55) and RSV (47), suggesting that depletion of free ubiquitin from the cytoplasm of mammalian cells disrupts retroviral budding and release. The role of ubiquitin in retroviral budding and release remains unclear.…”
mentioning
confidence: 99%